The Diffusion and Value of Healthcare Information Technology - Bower, Anthony G. (RAND Corporation, 2005)
This report characterizes the diffusion of use of electronic health records (EHRs). The author uses interviews and surveys and a literature review to investigate whether healthcare is expected to duplicate the gains enabled by information technology seen in several prominent industries. To accomplish this, the following questions are asked: What is the current diffusion of health information technology? How does EHR diffusion compare to innovations in other industries? What is such diffusion worth to society? What should the government do, if anything, to speed the adoption of EHRs?